PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS CANVA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS 5 MATA PELAJARAN IPAS MATERI TEKNOLOGI UNTUK KEHIDUPAN DI SDN BANJARSAWAH 1 - Fitri Wahyuni; Didit Yulian Kasdriyanto; Faridahtul Jannah (STKIP Subang, 2026)
This research and development project aims to produce an interactive learning medium based on Canva to improve student learning outcomes. This research and development project addresses challenges such as low student engagement, suboptimal learning outcomes, and traditional teaching methods in the IPAS (Natural Sciences and Social Sciences) subject for fifth-grade students at SDN Banjarsawah 1. Preliminary observations indicate that conventional teaching methods, which primarily rely on textbooks and blackboards, result in students becoming passive and unenthusiastic, with limited conceptual understanding of the “Technology for Life” material. To address these issues, this study aims to develop a Canva-based interactive learning medium that is valid, effective, practical, and suitable for improving learning outcomes, conceptual understanding, and student engagement in the IPAS subject. The research and development method employed the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), a systematic and structured approach to developing educational media. This interactive media integrates text, images, animations, videos, and interactive quizzes to make learning more engaging and easier to understand. The product has undergone validation by subject matter and media experts, as well as practical testing with fifth-grade teachers and students. The results of the research and development indicate that this media was rated as highly suitable by media experts (93.75%) and subject matter experts (95.83%). Student feedback during individual trials also showed a high level of practicality (91.66%), indicating increased motivation and better understanding. Post-test results showed a significant improvement in student learning outcomes, with an N-Gain score of 0.7192, which classifies this medium as “Highly Effective.” This demonstrates the positive impact of Canva-based interactive learning media in enhancing IPAS learning.